2012
DOI: 10.1002/sia.4844
|View full text |Cite
|
Sign up to set email alerts
|

Relation between the microstructure and microchemistry in Ni‐based superalloy

Abstract: dNi-based superalloys with biphasic structure (g + g′) are widely used for high-temperature applications, such as disks and blades of gas turbines and aeronautical engines. For these applications, the stability at high temperature is of utmost importance, in particular the coarsening and the morphological changes of g′ may be seriously detrimental for in-service components. Evolution of g′ particles strongly depends on the composition difference between disordered matrix and particles. The present work is devo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…It was also observed that carbides precipitated near the fusion boundary. Kaciulis et al 11 examined the microstructure and microchemistry of nickel-based super alloys with biphasic structure (gamma and gamma 0 phases), using SEM, AFS, PIXE and scanning photoemission microscopy (SPEM). The compositional differences between the two phases were elucidated through SPEM spectral images.…”
Section: Ferrous Metalsmentioning
confidence: 99%
“…It was also observed that carbides precipitated near the fusion boundary. Kaciulis et al 11 examined the microstructure and microchemistry of nickel-based super alloys with biphasic structure (gamma and gamma 0 phases), using SEM, AFS, PIXE and scanning photoemission microscopy (SPEM). The compositional differences between the two phases were elucidated through SPEM spectral images.…”
Section: Ferrous Metalsmentioning
confidence: 99%
“…Refractory elements, such as Re, Ta, Ru and W, are today added to Ni-based superalloys to improve their high temperature properties [145][146][147][148]. These elements provide good creep strength because their low atomic mobility retards dislocation climb in both γ and γ' phases.…”
Section: Microstructural Stabilitymentioning
confidence: 99%
“…After the EBW, the microstructural features in the MZ, HAZ, and base alloy have been investigated by micro‐hardness tests, observations of light optical microscopy (LOM) and scanning electron microscopy (SEM), X‐ray diffraction (XRD), X‐ray Photoelectron Spectroscopy (XPS), and Auger electron spectroscopy (AES), which have already demonstrated their effectiveness in studies of composition profiles connected to diffusion phenomena in superalloys …”
Section: Introductionmentioning
confidence: 99%